A Study Of The Effect Of Mindfulness Therapy On Anxiety In Adolescents (Journal of Namibian Studies : History Politics Culture, 2023)
Introduction: Adolescent anxiety is influenced by a variety of factors, and there is a need to develop more effective care and rehabilitation plans. Being an important component, mindfulness can play a major role in mental health in adolescents.Objective: The purpose of the study is to check the effect of mindfulness therapy on anxiety levels in adolescents. Methodology: Adolescents studying in Dehradun's private and public schools participated in this pre-posttest study. Written consents were obtained, and 120 study participants who met the inclusion and exclusion criteria were chosen from stratified data. Four groups were formed including 10 male and 10 female adolescents in each group. while 22 adolescents were excluded and 18 were kept in waiting list. The Beck anxiety inventory was utilized to gather data on anxiety. A total of 15 mindfulness sessions were employed for each group to control anxiety. A t-test was applied for statistical analysis.Findings: Initial anxiety level of adolescents was 48.90 in the extremely severe category.  After 15 mindfulness sessions, the subject’s anxiety degree was reduced by 82.11%. Conclusion: This investigation is a diagnostic study, which is aimed at managing the level of anxiety in adolescents. The study discovered that adolescents’ anxiety was reduced significantly following mindfulness. In general, it is found that mindfulness is useful in the management of adolescents’ anxiety.